PENGEMBANGAN MEDIA DIORAMA AUDIOVISUAL BERBASIS QR CODE DALAM PEMBELAJARAN SEJARAH PADA MATERI PROKLAMASI KEMERDEKAAN INDONESIA BAGI SISWA KELAS XI SMAS KHADIJAH SURABAYA - Febriana Salsabilla; Corry Liana (Lambung Mangkurat University, 2026)
History learning in schools often relies on conventional lecture methods and standard textbooks, causing students to remain passive and struggle with abstract historical concepts. Meanwhile, the utilization of digital devices remains sub-optimal, as they are mostly limited to accesing e-books and completing practice questions. This study aims to develop a QR Code-based Audiovisual Diorama on the proclamation of Indonesian independence material and determine its feasibility as an innovative learning source. Using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study involved students of student XI-5 at SMAS Khadijah Surabaya as research subjects. Qualitative data were gathered through observation and documentation, while quantitative data were collected via validation instrument and student response questionnaires. The results revealed that the developed media achieved a 75% feasibility score from media experts (feasible category) and 93,33% from materials expert (highly feasible category). Furthermore, student responses during the implementation phase reached an average score of 86,26%, placing it in the highly feasible category. In conclusion, the Qr Code-based Audiovisual Diorama is highly feasible for history learning and serves as an effective, interactive innovation for interactive learning sources in schools.